Glenn Gould and ‘Opus 2’: An outline for a musical understanding of contrapuntal radio with respect to The Idea of North - Cushing, Anthony (Circuit)

(untitled) (Les Presses de l’Université de Montréal, 2012)
The Idea of North is the first of Glenn Gould’s Solitude Trilogy documentaries. Like the two works that follow it in the trilogy, North attracts a significant amount of attention for its place in a nether region between Gould as a performer and Gould the intellectual. The bulk of the literature on the work debates categorizing it as documentary, radio drama/theatre, or music. Gould’s own descriptions of it encompass all three and render the task of pigeonholing the work difficult. This article will explore what makes The Idea of North musical. I contend that, even if considered as documentary, drama, or music, the work is musically conceived and musical and, as such, is a milestone for Gould in developing his compositional voice.